Regional Disparities in the Efficacy of Renewable Energy Development for Alleviating Energy Poverty in Indonesia: An In-depth Analysis - Gunawan, Ujang Hendra; Kadir, Nuraeni; Kadir, Abdul Rahman; Sobarsyah, Muhammad; Sabbar, Sabbar Dahham (International Journal of Energy Economics and Policy, 2024)
Existing studies have primarily focused on factors influencing energy poverty (EP), with limited attention given to the specific role of renewable energy advancements (REA). This study addresses this gap by employing a moment quantile regression model to evaluate the energy poverty index system, exploring the impact of REA on EP. Data is sourced from a 30-province panel in Indonesia from 2003 to 2019. The study reveals that REA contributes to alleviating EP, particularly in regions with low climate vulnerability. Both linear and non-linear models indicate that the climate vulnerability index (CVI) moderates this relationship, with REA reducing EP in low CVI regions, but showing the opposite effect under high CVI conditions. This effect is geographically concentrated in western Indonesia, with no significant impact in central and eastern regions. These findings provide valuable insights for strategies aimed at reducing energy poverty and promoting sustainable energy growth.